Heat-absorbing and heat-insulating coating for solar power generation glass and preparation process thereof
The heat-insulating coating prepared by the core-shell structure particles of iron tetraoxide-copper manganese oxide prepared by the hydrothermal calcination method and composite heat-insulating coatings prepared by the composite heat-insulating body on solar power generation glass have solved the shortcomings of the existing paints in terms of heat-insulating properties, achieved efficient solar energy absorption and heat-insulating effects, and improved power generation efficiency.
Patent Information
- Application Number
- CN202510369006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-06-17
AI Technical Summary
The existing coatings for solar power generation glasses have shortcomings in thermal insulation performance, which cannot effectively improve the absorption efficiency of solar energy and reduce heat loss, resulting in low power generation efficiency.
The core-shell structure particles of iron trioxide-copper manganese oxide were prepared by hydrothermal calcining, and combined with hydrophobically modified silica aerogel and amino-modified hollow glass microbeads, forming a composite heat insulator, which was used to prepare heat-insulating coatings.
It significantly improves the absorption efficiency of solar energy, reduces thermal radiation loss, enhances thermal insulation performance, and improves the energy utilization rate and power generation efficiency of solar power glass.
Smart Images

Figure CN120158172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating preparation, and particularly relates to a heat-absorbing and heat-insulating coating for solar power generation glass and a preparation process thereof. Background Art
[0002] With the continuous growth of global demand for clean energy, solar energy, as a clean and renewable energy source, has received extensive attention and rapid development in its utilization technology. As one of the key components for solar energy utilization, solar power generation glass plays an important role in the field of photovoltaic power generation. It can convert solar energy into electrical energy and provide power support for various facilities.
[0003] However, solar power generation glass faces many challenges in practical applications. Among them, how to effectively improve its absorption efficiency of solar energy while reducing the heat transfer to the surrounding environment to enhance the power generation efficiency and maintain the stable operation of the equipment has become an urgent problem to be solved. The existing coatings for solar power generation glass have obvious deficiencies in heat absorption and insulation performance. Some coatings can absorb a certain amount of solar energy, but the heat insulation effect is not good, resulting in a large amount of heat loss and reducing the power generation efficiency; while some other coatings have certain heat insulation ability, but the absorption efficiency of solar energy is low, and the solar energy resources cannot be fully utilized.
[0004] Therefore, the research and development of a heat-absorbing and heat-insulating coating for solar power generation glass and a preparation process thereof have important practical significance and broad market prospects. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide a heat-absorbing and heat-insulating coating for solar power generation glass and a preparation process thereof.
[0006] A preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass comprises the following steps: S1: Preparation of magnetite magnetic nanoparticles S2: Preparation of magnetite - copper manganese oxide core - shell structure particles Use ethylene glycol, deionized water, copper nitrate and manganese nitrate to prepare a precursor solution, and then prepare precursor particles by mixing and reacting magnetite magnetic nanoparticles with the precursor solution. Place the precursor particles in a tubular furnace for high-temperature reaction to obtain magnetite - copper manganese oxide core - shell structure particles; S3: Preparation of hydrophobic modified silica aerogel Use hexamethyldisilazane to modify silica aerogel to prepare hydrophobic modified silica aerogel; S4: Preparation of amino - modified hollow glass microspheres The hollow glass microspheres were further modified with γ-aminopropyltriethoxysilane to obtain amino-modified hollow glass microspheres; S5: Preparation of the heat-absorbing and heat-insulating coating The hydrophobic modified silica aerogel and the amino-modified hollow glass microspheres were ball-milled to prepare a composite heat-insulating body. Then, 0 - 30 parts by weight of an acrylic resin emulsion, 10 - 20 parts by weight of a waterborne polyurethane, 0.05 - 0.12 parts by weight of a polyester-modified silicone, 23 - 28 parts by weight of the composite heat-insulating body, 14 - 23 parts by weight of the Fe₃O₄-CuMn oxide core-shell structure particles, 3 - 9 parts by weight of glycerol fatty acid ester, 2 - 7 parts by weight of phenethyl alcohol oleate, and 12 - 18 parts by weight of deionized water were mixed and stirred to obtain the heat-absorbing and heat-insulating coating.
[0007] Further, the preparation of the Fe₃O₄ magnetic nanoparticles in step S1 specifically includes the following steps: S1.1: 1.1 - 1.3 parts by weight of sodium citrate dihydrate, 0.54 - 0.61 parts by weight of ferric chloride hexahydrate, 0.3 - 0.6 parts by weight of polyacrylamide, and 0.36 - 0.42 parts by weight of urea were added to 40 - 50 parts by weight of deionized water, and stirred and mixed for 20 - 30 min to obtain a mixture; S1.2: The mixture was poured into the polytetrafluoroethylene liner of a stainless-steel autoclave, and then placed in an oven at 200 - 230 °C for reaction for 12 - 13 h to obtain a suspension. The black magnetic nanoparticles were magnetically separated and recovered from the suspension by a magnet, washed 2 - 3 times with ultrapure water, and then dried to obtain the Fe₃O₄ magnetic nanoparticles.
[0008] Further, the preparation of the Fe₃O₄-CuMn oxide core-shell structure particles in step S2 specifically includes the following steps: S2.1: Ethylene glycol and deionized water were mixed in a volume ratio of 1:1, and then copper nitrate and manganese nitrate were added, and stirred and mixed evenly to obtain a precursor solution. The concentration of copper nitrate in the precursor solution was 0.1 mol / L, and the concentration of manganese nitrate was 0.15 mol / L; S2.2: 1 - 2 parts by weight of the Fe₃O₄ magnetic nanoparticles were added to 20 - 30 parts by weight of the precursor solution, ultrasonically treated for 20 - 30 min, and then stirred at 50 - 55 °C for 4 - 5 h. During the stirring, the pH was adjusted to 5 by ammonia water. After the stirring ended, the temperature was raised to 80 - 85 °C, and then a 0.1 mol / L EDTA disodium salt solution was added. The 0.1 mol / L EDTA disodium salt solution accounted for 5% of the total volume, and stirred for 2 - 3 h. Finally, centrifuged at 8000 - 9000 rpm for 5 - 10 min, and the centrifuged precipitate was dried at 60 - 65 °C for 12 - 14 h to obtain the precursor particles; S2.3: Place the precursor particles in a tubular furnace, heat them from room temperature to 400 - 420 °C at a rate of 5 - 8 °C / min, hold for 2 - 3 h, then continue to heat to 600 - 620 °C at a rate of 2 - 3 °C / min, hold for 1 - 2 h, and finally cool to 180 - 200 °C in the furnace and then take them out and let them cool naturally to room temperature to obtain Fe₃O₄-CuMn oxide core-shell structure particles.
[0009] Further, the preparation of the hydrophobic modified silica aerogel in step S3 specifically includes the following steps: S3.1: Mix 1 - 2 parts by weight of tetraethyl orthosilicate and 0.2 - 0.5 parts by weight of methyltrimethoxysilane, then add 5 - 8 parts by weight of a hydrochloric acid solution with a concentration of 0.1 mol / L, stir at room temperature for 1 - 2 h, then add 2 - 3 parts by weight of ammonia water and 1 - 2 parts by weight of N,N-dimethylformamide and continue to stir for 2 - 3 min, and finally seal at room temperature to form a wet gel. S3.2: After aging the wet gel at room temperature for 24 - 26 h, soak the aged gel in a n-hexane solution in a vacuum drying oven at 30 - 33 °C, with a liquid-solid volume ratio of 5:1, let it stand for 6 - 7 h, repeat 2 - 3 times to obtain the treated gel. Place the gel after solvent replacement in a sealed container, place a 10 wt% hexamethyldisilazane-ethanol solution at the bottom, with a volume of 1 / 5 of the container, then treat it in a vacuum drying oven at 30 - 33 °C for 8 - 10 h, and finally wash with ethanol to obtain the hydrophobic modified silica aerogel.
[0010] Further, the preparation of the amino-modified hollow glass microspheres in step S4 specifically includes the following steps: S4.1: Soak the hollow glass microspheres with a particle size of 5 - 10 μm, a wall thickness of 0.5 - 1 μm, and a density of 0.15 - 0.25 g / cm 3 in 5 wt% dilute hydrochloric acid and ultrasonically treat for 20 - 30 min, then wash with deionized water until neutral, and dry at 90 - 100 °C for 2 - 3 h to obtain the washed hollow glass microspheres. S4.2: Mix γ-aminopropyltriethoxysilane and 60 wt% ethanol aqueous solution at a volume ratio of 1:10 - 12, then magnetically stir for 30 - 40 min, and adjust the pH to 5 with acetic acid to obtain a hydrolyzed silane solution. S4.3: Add 1 - 2 parts by weight of the washed hollow glass microspheres to 50 - 60 parts by weight of the hydrolyzed silane solution, then stir and react at 60 - 70 °C for 5 - 6 h, then centrifuge at 5000 - 6000 rpm for 5 - 10 min, and finally wash 2 - 3 times with deionized water and dry to obtain the amino-modified hollow glass microspheres.
[0011] Further, the preparation of the heat-absorbing and heat-insulating coating in step S4 specifically includes the following steps: S5.1: Put 3 - 5 parts by weight of hydrophobically modified silica aerogel and 1 - 2 parts by weight of amino - modified hollow glass microspheres into a planetary ball - milling jar. Use zirconia balls with a diameter of 3 mm, with a ball - to - material ratio of 5:1. Ball - mill at 300 - 500 rpm for 2 - 3 h, with intermittent forward and reverse rotation, 10 min forward and 2 min reverse. Then add 0.5 wt% polyethylene glycol and continue ball - milling for 30 - 40 min to obtain a composite thermal insulation body after ball - milling; S5.2: Mix 20 - 30 parts by weight of acrylic resin emulsion, 10 - 20 parts by weight of waterborne polyurethane, 0.05 - 0.12 parts by weight of polyester - modified silicone oxygen alkane, 23 - 28 parts by weight of the composite thermal insulation body, 14 - 23 parts by weight of Fe₃O₄ - CuMn oxide core - shell structure particles, 3 - 9 parts by weight of fatty acid glyceride, 2 - 7 parts by weight of phenyl ethanol oleate, and 12 - 18 parts by weight of deionized water and stir to obtain a heat - absorbing and heat - insulating coating.
[0012] A heat - absorbing and heat - insulating coating for solar power generation glass, characterized in that it is prepared by the preparation process of a heat - absorbing and heat - insulating coating for solar power generation glass described in any one of the above.
[0013] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The core-shell structure particles prepared by the hydrothermal-calcination method are adopted in the present invention. The inner core is a magnetic nanosphere, which can enhance the photothermal conversion efficiency. In solar power generation glass, this means that the absorbed light energy can be converted into heat energy more effectively, improving the utilization efficiency of solar energy. As a result, the solar power generation glass can absorb more solar energy per unit time and convert it into useful energy, thereby enhancing the power generation efficiency and obtaining more heat energy output in the photothermal utilization scenario. The outer shell is a copper-manganese oxide doped layer, and the thermal radiation loss is reduced by regulating oxygen vacancies. During the solar power generation process, reducing the thermal radiation loss can enable the absorbed heat to be better retained in the glass system and reduce the heat dissipation to the surrounding environment. This not only helps to maintain the temperature of the glass surface, ensuring the continuous progress of photothermal conversion, but also avoids energy waste caused by excessive heat dissipation, improving the energy utilization efficiency of the entire system. The core-shell structure enables ultraviolet-visible-near-infrared broadband absorption and can capture solar radiation energy in a wider range. Compared with ordinary materials that can only absorb light in specific wavelength bands, the core-shell structure particles can make full use of various energies in the solar spectrum without missing the light energy in each wavelength band, thus significantly increasing the total amount of solar energy absorbed and further improving the energy utilization rate of the solar power generation glass. In addition, the coating prepared by adding the core-shell structure nanoparticles has good heat insulation performance. On the one hand, it can reduce the transfer of external heat to the inside of the glass, protecting the equipment or space inside the glass from the influence of high temperature; on the other hand, it can also prevent the excessive diffusion of heat generated by photothermal conversion inside the glass, thereby maintaining the temperature stability of the glass surface and being beneficial to improving the performance and service life of the solar power generation glass.
[0014] 2. The hydrophobic modified silica aerogel in the present invention has an extremely low thermal conductivity and is an excellent heat insulation material that can effectively prevent heat conduction. The amino-modified hollow glass microspheres have a hollow structure inside, and there is a large amount of air. The poor thermal conductivity of air further enhances the heat insulation effect. The composite heat insulation body formed by combining the two is used in the coating. The aerogel nanopores and the microsphere macroscopic cavities form a "dual-scale heat insulation network", which can significantly reduce the heat conduction of the solar power generation glass, reduce the heat transfer from one side of the glass to the other side, maintain the temperature difference between the two sides of the glass, and improve the heat insulation performance of the glass, which is beneficial to improving the power generation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings incorporated herein and constituting a part of the specification illustrate embodiments of the present invention and, together with the specification, are further used to explain the principles of the present invention and enable those skilled in the relevant art to implement and use the present invention.
[0016] Figure 1 It is a process flow chart of the preparation of a heat-absorbing and heat-insulating coating for a solar power generation glass adopted in an embodiment of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0017] The preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass provided by the present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it should be noted here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments. For some well-known technologies, those skilled in the art can also adopt other alternative methods for implementation; moreover, the accompanying drawings are only for more specifically describing the embodiments and are not intended to specifically limit the present invention. Embodiment
[0018] The preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass is as Figure 1 shown and includes the following steps: S1: Preparation of magnetite magnetic nanoparticles S1.1: Add 1.1 parts by weight of sodium citrate dihydrate, 0.54 parts by weight of ferric chloride hexahydrate, 0.3 parts by weight of polyacrylamide, and 0.36 parts by weight of urea to 40 parts by weight of deionized water, stir and mix for 20 min to obtain a mixture; S1.2: Pour the mixture into the polytetrafluoroethylene liner of a stainless steel autoclave, then place it in an oven at 200 °C for reaction for 12 h to obtain a suspension. Magnetically separate and recover the black magnetic nanoparticles from the suspension with a magnet, wash them twice with ultrapure water, and then dry to obtain magnetite magnetic nanoparticles; S2: Preparation of magnetite - copper manganese oxide core - shell structure particles S2.1: Mix ethylene glycol and deionized water in a volume ratio of 1:1, then add copper nitrate and manganese nitrate, stir and mix evenly to obtain a precursor solution. The concentration of copper nitrate in the precursor solution is 0.1 mol / L, and the concentration of manganese nitrate is 0.15 mol / L; S2.2: Add 1 part by weight of magnetite magnetic nanoparticles to 20 parts by weight of the precursor solution, ultrasonically treat for 20 min, then stir at 50 °C for 4 h. During stirring, adjust the pH to 5 with ammonia water. After stirring ends, raise the temperature to 80 °C, then dropwise add 0.1 mol / L disodium EDTA solution, and the 0.1 mol / L disodium EDTA solution accounts for 5% of the total volume. Stir for 2 h, and finally centrifuge at 8000 rpm for 5 min. Dry the centrifuged precipitate at 60 °C for 12 h to obtain precursor particles; S2.3: Place the precursor particles in a tubular furnace, raise the temperature to 400 °C at a rate of 5 °C / min, hold for 2 h, continue to raise the temperature to 600 °C at a rate of 2 °C / min, hold for 1 h, and finally take it out after cooling to 180 °C with the furnace and naturally cool to room temperature to obtain magnetite - copper manganese oxide core - shell structure particles; S3: Preparation of hydrophobic modified silica aerogel S3.1: Mix 1 part by weight of tetraethyl orthosilicate and 0.2 part by weight of methyltrimethoxysilane, then add 5 parts by weight of a hydrochloric acid solution with a concentration of 0.1 mol / L. After that, stir at room temperature for 1 h, then add 2 parts by weight of ammonia water and 1 part by weight of N,N-dimethylformamide and continue stirring for 2 min. Finally, seal at room temperature to form a wet gel; S3.2: After aging the wet gel at room temperature for 24 h, soak the aged gel in a n-hexane solution in a vacuum drying oven at 30 °C with a liquid-solid volume ratio of 5:1, let it stand for 6 h, and repeat 2 times to obtain the treated gel. Place the gel after solvent replacement in a sealed container, place a 10 wt% hexamethyldisilazane-ethanol solution at the bottom with a volume of 1 / 5 of the container, then treat it in a vacuum drying oven at 30 °C for 8 h, and finally rinse with ethanol to obtain a hydrophobic modified silica aerogel; S4: Preparation of amino-modified hollow glass microspheres S4.1: Soak hollow glass microspheres with a particle size of 5 μm, a wall thickness of 0.5 μm, and a density of 0.15 g / cm 3 in 5 wt% dilute hydrochloric acid and ultrasonically treat for 20 min, then wash with deionized water until neutral and dry at 90 °C for 2 h to obtain the washed hollow glass microspheres; S4.2: Mix γ-aminopropyltriethoxysilane and a 60 wt% ethanol aqueous solution in a volume ratio of 1:10, then magnetically stir for 30 min and adjust the pH to 5 with acetic acid to obtain a hydrolyzed silane solution; S4.3: Add 1 part by weight of the washed hollow glass microspheres to 50 - 60 parts by weight of the hydrolyzed silane solution, then stir and react at 60 °C for 5 h, then centrifuge at 5000 rpm for 5 min, and finally wash twice with deionized water and dry to obtain amino-modified hollow glass microspheres; S5: Preparation of heat-absorbing and heat-insulating coating S5.1: Put 3 parts by weight of the hydrophobic modified silica aerogel and 1 part by weight of the amino-modified hollow glass microspheres into a planetary ball milling tank, use zirconia balls with a diameter of 3 mm, with a ball-to-material ratio of 5:1, ball mill at 300 rpm for 2 h, alternate forward and reverse rotation, 10 min forward, 2 min reverse, then add 0.5 wt% polyethylene glycol and continue ball milling for 30 min to obtain a composite heat-insulating body; S5.2: Mix 20 parts by weight of acrylic resin emulsion, 10 parts by weight of waterborne polyurethane, 0.05 part by weight of polyester-modified silicone oxide, 23 parts by weight of the composite heat-insulating body, 14 parts by weight of the Fe₃O₄-CuMn₂O₄ core-shell structure particles, 3 parts by weight of fatty acid glyceride, 2 parts by weight of phenyl ethanol oleate, and 12 parts by weight of deionized water and stir to obtain the heat-absorbing and heat-insulating coating. Examples
[0019] A preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass, as Figure 1 shown, includes the following steps: S1: Preparation of magnetite magnetic nanoparticles S1.1: Add 1.1 parts by weight of sodium citrate dihydrate, 0.54 parts by weight of ferric chloride hexahydrate, 0.3 parts by weight of polyacrylamide, and 0.36 parts by weight of urea to 40 parts by weight of deionized water, stir and mix for 30 min to obtain a mixture; S1.2: Pour the mixture into the polytetrafluoroethylene lining of a stainless steel autoclave, then place it in an oven at 230 °C and react for 13 h to obtain a suspension. Magnetically separate and recover the black magnetic nanoparticles from the suspension with a magnet, wash them 3 times with ultrapure water, and then dry to obtain magnetite magnetic nanoparticles; S2: Preparation of magnetite - copper manganese oxide core - shell structure particles S2.1: Mix ethylene glycol and deionized water in a volume ratio of 1:1, then add copper nitrate and manganese nitrate, stir and mix evenly to obtain a precursor solution. The concentration of copper nitrate in the precursor solution is 0.1 mol / L, and the concentration of manganese nitrate is 0.15 mol / L; S2.2: Add 1 part by weight of magnetite magnetic nanoparticles to 20 parts by weight of the precursor solution, ultrasonically treat for 30 min, then stir at 55 °C for 5 h. During stirring, adjust the pH to 5 with ammonia water. After stirring, raise the temperature to 85 °C, then dropwise add 0.1 mol / L EDTA disodium salt solution, and the 0.1 mol / L EDTA disodium salt solution accounts for 5% of the total volume. Stir for 3 h, and finally centrifuge at 9000 rpm for 10 min. Dry the centrifuged precipitate at 65 °C for 14 h to obtain precursor particles; S2.3: Place the precursor particles in a tubular furnace, raise the temperature to 420 °C at a rate of 8 °C / min, hold for 3 h, continue to raise the temperature to 620 °C at a rate of 3 °C / min, hold for 2 h, and finally cool in the furnace to 200 °C and then take out, and naturally cool to room temperature to obtain magnetite - copper manganese oxide core - shell structure particles; S3: Preparation of hydrophobic modified silica aerogel S3.1: Mix 1 part by weight of tetraethyl orthosilicate and 0.2 part by weight of methyltrimethoxysilane, then add 5 parts by weight of hydrochloric acid solution with a concentration of 0.1 mol / L, then stir at room temperature for 2 h, add 2 parts by weight of ammonia water and 1 part by weight of N, N - dimethylformamide and continue to stir for 3 min, and finally seal at room temperature to form a wet gel; S3.2: After aging the wet gel at room temperature for 26 h, soak the aged gel in a n-hexane solution in a vacuum drying oven at 33 °C with a liquid-solid volume ratio of 5:1, let it stand for 7 h, and repeat 3 times to obtain the treated gel. Place the gel after solvent replacement in a sealed container, put 10 wt% hexamethyldisilazane-ethanol solution at the bottom with a volume of 1 / 5 of the container, and then treat it in a vacuum drying oven at 33 °C for 10 h. Finally, rinse it with ethanol to obtain hydrophobic modified silica aerogel; S4: Preparation of amino-modified hollow glass microspheres S4.1: Soak hollow glass microspheres with a particle size of 10 μm, a wall thickness of 1 μm, and a density of 0.25 g / cm 3 in 5 wt% dilute hydrochloric acid and ultrasonically treat for 30 min, then wash with deionized water until neutral, and dry at 100 °C for 3 h to obtain the washed hollow glass microspheres; S4.2: Mix γ-aminopropyltriethoxysilane with 60 wt% ethanol aqueous solution at a volume ratio of 1:10, then magnetically stir for 40 min and adjust the pH to 5 with acetic acid to obtain a hydrolyzed silane solution; S4.3: Add 1 part by weight of the washed hollow glass microspheres to 50 parts by weight of the hydrolyzed silane solution, then stir and react at 70 °C for 6 h, then centrifuge at 6000 rpm for 10 min, and finally wash 3 times with deionized water and dry to obtain amino-modified hollow glass microspheres; S5: Preparation of heat-absorbing and heat-insulating coating S5.1: Put 3 parts by weight of hydrophobic modified silica aerogel and 1 part by weight of amino-modified hollow glass microspheres into a planetary ball milling tank, use zirconia balls with a diameter of 3 mm, with a ball-to-material ratio of 5:1, ball mill at 500 rpm for 3 h, alternate forward and reverse rotation, 10 min forward and 2 min reverse, then add 0.5 wt% polyethylene glycol and continue ball milling for 40 min to obtain a composite heat-insulating body; S5.2: Mix 20 parts by weight of acrylic resin emulsion, 10 parts by weight of waterborne polyurethane, 0.05 part by weight of polyester-modified silicone oxide, 23 parts by weight of the composite heat-insulating body, 14 parts by weight of Fe₃O₄-CuMn oxide core-shell structure particles, 3 parts by weight of fatty acid glyceride, 2 parts by weight of phenyl ethanol oleate and 12 parts by weight of deionized water and stir to obtain a heat-absorbing and heat-insulating coating. Examples
[0020] A preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass, as Figure 1 shown, includes the following steps: S1: Preparation of Fe₃O₄ magnetic nanoparticles S1.1: Add 1.3 parts by weight of sodium citrate dihydrate, 0.61 parts by weight of ferric chloride hexahydrate, 0.6 parts by weight of polyacrylamide, and 0.42 parts by weight of urea to 50 parts by weight of deionized water, stir and mix for 20 min to obtain a mixture; S1.2: Pour the mixture into the polytetrafluoroethylene liner of a stainless-steel autoclave, then place it in an oven at 200 °C and react for 12 h to obtain a suspension. Magnetically separate and recover the black magnetic nanoparticles from the suspension with a magnet, wash twice with ultrapure water, and then dry to obtain magnetite magnetic nanoparticles; S2: Preparation of magnetite-copper manganese oxide core-shell structure particles S2.1: Mix ethylene glycol and deionized water in a volume ratio of 1:1, then add copper nitrate and manganese nitrate, stir and mix evenly to obtain a precursor solution. The concentration of copper nitrate in the precursor solution is 0.1 mol / L, and the concentration of manganese nitrate is 0.15 mol / L; S2.2: Add 2 parts by weight of magnetite magnetic nanoparticles to 30 parts by weight of the precursor solution, ultrasonically treat for 20 min, then stir at 50 °C for 4 h. During stirring, adjust the pH to 5 with ammonia water. After stirring ends, raise the temperature to 80 °C, then dropwise add 0.1 mol / L disodium ethylenediaminetetraacetate solution, and the 0.1 mol / L disodium ethylenediaminetetraacetate solution accounts for 5% of the total volume. Stir for 2 h, and finally centrifuge at 8000 rpm for 5 min. Dry the centrifuged precipitate at 60 °C for 12 h to obtain precursor particles; S2.3: Place the precursor particles in a tubular furnace, raise the temperature to 400 °C at a rate of 5 °C / min, hold for 2 h, continue to raise the temperature to 600 °C at a rate of 2 °C / min, hold for 1 h, and finally take it out after cooling to 180 °C with the furnace and naturally cool to room temperature to obtain magnetite-copper manganese oxide core-shell structure particles; S3: Preparation of hydrophobic modified silica aerogel S3.1: Mix 2 parts by weight of tetraethyl orthosilicate and 0.5 parts by weight of methyltrimethoxysilane, then add 8 parts by weight of a hydrochloric acid solution with a concentration of 0.1 mol / L, stir at room temperature for 1 h, add 3 parts by weight of ammonia water and 2 parts by weight of N,N-dimethylformamide, continue to stir for 2 min, and finally seal at room temperature to form a wet gel; S3.2: After aging the wet gel at room temperature for 24 h, soak the aged gel in a n-hexane solution in a 30 °C vacuum drying oven with a liquid-solid volume ratio of 5:1, let it stand for 6 h, repeat 2 times to obtain a treated gel. Place the gel after solvent replacement in a closed container, place a 10 wt% hexamethyldisilazane-ethanol solution at the bottom, with a volume of 1 / 5 of the container, then treat it in a 30 °C vacuum drying oven for 8 h, and finally wash with ethanol to obtain hydrophobic modified silica aerogel; S4: Preparation of Amino-Modified Hollow Glass Microspheres S4.1: Immerse hollow glass microspheres with a particle size of 5 μm, a wall thickness of 0.5 μm, and a density of 0.15 g / cm 3 in 5 wt% dilute hydrochloric acid and ultrasonically treat for 20 min. Then wash with deionized water until neutral and dry at 90 °C for 2 h to obtain washed hollow glass microspheres; S4.2: Mix γ-aminopropyltriethoxysilane with a 60 wt% ethanol aqueous solution at a volume ratio of 1:12, then magnetically stir for 30 min and adjust the pH to 5 with acetic acid to obtain a hydrolyzed silane solution; S4.3: Add 2 parts by weight of the washed hollow glass microspheres to 60 parts by weight of the hydrolyzed silane solution, then stir and react at 60 °C for 5 h. Then centrifuge at 5000 rpm for 5 min, and finally wash twice with deionized water and dry to obtain amino-modified hollow glass microspheres; S5: Preparation of Heat-Absorbing and Heat-Insulating Coating S5.1: Put 5 parts by weight of hydrophobically modified silica aerogel and 2 parts by weight of amino-modified hollow glass microspheres into a planetary ball mill jar. Use zirconia balls with a diameter of 3 mm, a ball-to-material ratio of 5:1, and ball mill at 300 rpm for 2 h, with intermittent forward and reverse rotation, 10 min forward and 2 min reverse. Then add 0.5 wt% polyethylene glycol and continue ball milling for 30 min to obtain a composite heat-insulating body after ball milling; S5.2: Mix 30 parts by weight of acrylic resin emulsion, 20 parts by weight of waterborne polyurethane, 0.12 parts by weight of polyester-modified silicone oxide, 28 parts by weight of the composite heat-insulating body, 23 parts by weight of Fe₃O₄-CuMn oxide core-shell structure particles, 9 parts by weight of fatty acid glyceride, 7 parts by weight of phenyl ethanol oleate, and 18 parts by weight of deionized water and stir to obtain a heat-absorbing and heat-insulating coating.
[0021] Comparative Example 1 Compared with Example 1, the difference in Comparative Example 1 is that Comparative Example 1 is a commercially available heat-absorbing coating, denoted as Comparative Example 1.
[0022] Comparative Example 2 Compared with Example 1, the difference in Comparative Example 2 is that Comparative Example 2 is prepared by removing the Fe₃O₄-CuMn oxide core-shell structure particles in Steps S1-S2 and S5.2, and the remaining steps remain unchanged to obtain a heat-absorbing and heat-insulating coating, denoted as Comparative Example 2.
[0023] Comparative Example 3 Compared with Example 1, the difference in Comparative Example 3 is that Comparative Example 3 is prepared by removing Steps S3 and S5.1, and replacing the composite heat-insulating body in Step S5.2 with amino-modified hollow glass microspheres, and the remaining steps remain unchanged to obtain a heat-absorbing and heat-insulating coating, denoted as Comparative Example 3.
[0024] Comparative Example 4 Compared with Example 1, the difference in Comparative Example 4 is that steps S4 and S5.1 are removed, and the composite heat insulation body in step S5.2 is replaced with hydrophobically modified silica aerogel, and the remaining steps remain unchanged to prepare the heat-absorbing and heat-insulating coating, denoted as Comparative Example 4.
[0025] Comparative Example 5 Compared with Example 1, the difference in Comparative Example 5 is that steps S3 - S4, S5.1 and the composite heat insulation body in step S5.2 are removed, and the remaining steps remain unchanged to prepare the heat-absorbing and heat-insulating coating, denoted as Comparative Example 5.
[0026] The heat-absorbing and heat-insulating coatings prepared in Examples 1 - 3 and Comparative Examples 1 - 5 were subjected to performance measurement, and the measurement results are shown in Table 1 for reference.
[0027] Table 1. Performance measurement of Examples 1 - 3 and Comparative Examples 1 - 5 Solar absorptance (%) Thermal conductivity (W / m·K) Example 1 96.2 0.126 Example 2 97.1 0.121 Example 3 96.6 0.124 Comparative Example 1 83.2 0.322 Comparative Example 2 75.4 0.213 Comparative Example 3 88.4 0.291 Comparative Example 4 89.3 0.283 Comparative Example 5 83.3 0.332 It can be seen from the data in Table 1 that the solar absorptance of the examples is higher than that of Comparative Example 1, and the thermal conductivity is lower than that of Comparative Example 1, indicating that the heat-absorbing and heat-insulating coating prepared by the present invention has good heat-absorbing performance and heat-insulating effect. It can be seen from the data of Comparative Example 2 that the addition of the Fe₃O₄-CuMn oxide core-shell structure particles significantly increases the total amount of solar energy absorbed, further improving the energy utilization rate of the solar power generation glass, and the coating prepared by adding the core-shell structure nanoparticles has good heat-insulating performance. It can be seen from the data of Comparative Examples 3 - 5 that the composite heat insulation body formed by the combination of hydrophobically modified silica aerogel and amino-modified hollow glass microspheres used in the coating can significantly reduce the heat conduction of the solar power generation glass and improve the heat-insulating performance of the glass.
[0028] The above examples are only illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Any person familiar with this technology can modify or change the above examples without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical idea disclosed by the present invention should still be covered by the claims of the present invention.
Claims
1. A preparation process of a heat-absorbing and heat-insulating coating for solar power generation glass, characterized in that: The steps include: S1: Preparation of FeO4 magnetic nanoparticles S2: Preparation of Fe3O4-CuMnO4 core-shell structure particles A precursor solution is prepared by using ethylene glycol, deionized water, copper nitrate and manganese nitrate, and then precursor particles are prepared by mixing ferroferric oxide magnetic nanoparticles with the precursor solution, and the precursor particles are placed in a tube furnace for high-temperature reaction to obtain ferroferric oxide-copper manganese oxide core-shell structure particles; S3: Preparation of hydrophobically modified silica aerogel Hexamethyldisilazane was used to modify silica aerogel to prepare hydrophobically modified silica aerogel; S4: Preparation of amino-modified hollow glass microspheres The hollow glass microspheres are further modified by using γ-aminopropyltriethoxysilane to obtain amino-modified hollow glass microspheres; S5: Preparation of heat-absorbing and heat-insulating coatings A composite thermal insulator is prepared by ball-milling hydrophobically modified silica aerogel and amino-modified hollow glass microbeads, and then 0-30 parts by weight of acrylic resin emulsion, 10-20 parts by weight of aqueous polyurethane, 0.05-0.12 parts by weight of polyester-modified organosiloxane, 23-28 parts by weight of composite thermal insulator, 14-23 parts by weight of ferrosoferric oxide-copper manganese oxide core-shell structure particles, 3-9 parts by weight of fatty acid glyceride, 2-7 parts by weight of phenylethyl oleate and 12-18 parts by weight of deionized water are mixed and stirred to obtain a heat-absorbing and heat-insulating coating.
2. The preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass according to claim 1, characterized in that: Step S1: Preparation of ferroferric oxide magnetic nanoparticles, specifically comprising the following steps: S1.1: adding 1.1-1.3 parts by weight of sodium citrate dihydrate, 0.54-0.61 parts by weight of ferric chloride hexahydrate, 0.3-0.6 parts by weight of polyacrylamide and 0.36-0.42 parts by weight of urea to 40-50 parts by weight of deionized water, stirring and mixing for 20-30 minutes to obtain a mixture; S1.2: Pour the mixture into the polytetrafluoroethylene liner of a stainless steel autoclave, and then place it in an oven at 200-230°C to react for 12-13 hours to obtain a suspension. Use a magnet to magnetically separate and recover the black magnetic nanoparticles from the suspension, wash them with ultrapure water for 2-3 times, and then dry them to obtain ferroferric oxide magnetic nanoparticles.
3. The preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass according to claim 2, characterized in that: Step S2: Preparation of ferroferric oxide-copper manganese oxide core-shell structure particles, specifically comprising the following steps: S2.1: Ethylene glycol and deionized water are mixed in a volume ratio of 1:1, and copper nitrate and manganese nitrate are added thereto, and the mixture is stirred and mixed to obtain a precursor solution, wherein the concentration of copper nitrate in the precursor solution is 0.1 mol / L, and the concentration of manganese nitrate is 0.15 mol / L; S2.2: 1-2 parts by weight of ferrosoferric oxide magnetic nanoparticles are added to 20-30 parts by weight of the precursor solution, and ultrasonically treated for 20-30 minutes, and then stirred at 50-55°C for 4-5 hours. During the stirring period, the pH is adjusted to 5 with ammonia water. After the stirring is completed, the temperature is raised to 80-85°C, and then 0.1 mol / LEDTA disodium salt solution is added dropwise, and the 0.1 mol / LEDTA disodium salt solution accounts for 5% of the total volume. Stir for 2-3 hours, and finally centrifuge at 8000-9000 rpm for 5-10 minutes. The precipitate after centrifugation is dried at 60-65°C for 12-14 hours to obtain precursor particles; S2.3: Place the precursor particles in a tubular furnace, raise the temperature to 400-420°C at 5-8°C / min, keep warm for 2-3h, continue to raise the temperature to 600-620°C at 2-3°C / min, keep warm for 1-2h, finally cool to 180-200°C in the furnace, take out, and cool naturally to room temperature to obtain ferroferric oxide-copper manganese oxide core-shell structure particles.
4. The preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass according to claim 3, characterized in that: Step S3: Preparation of hydrophobically modified silica aerogel, specifically comprising the following steps: S3.1: 1-2 parts by weight of tetraethyl orthosilicate and 0.2-0.5 parts by weight of methyltrimethoxysilane are mixed, and then 5-8 parts by weight of a 0.1 mol / L hydrochloric acid solution is added, followed by stirring at room temperature for 1-2 hours, and then 2-3 parts by weight of ammonia water and 1-2 parts by weight of N,N-dimethylformamide are added and stirred for 2-3 minutes, and finally sealed at room temperature to form a wet gel; S3.2: After the wet gel is aged at room temperature for 24-26 hours, the aged gel is soaked in n-hexane solution in a vacuum drying oven at 30-33°C, with a liquid-to-solid volume ratio of 5:1, and allowed to stand for 6-7 hours. Repeat 2-3 times to obtain the treated gel. The gel after solvent replacement is placed in a sealed container, and a 10wt% hexamethyldisilazane-ethanol solution is placed at the bottom, with the volume of 1 / 5 of the container. It is then treated in a vacuum drying oven at 30-33°C for 8-10 hours, and finally rinsed with ethanol to obtain a hydrophobically modified silica aerogel.
5. The preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass according to claim 4, characterized in that: Step S4: Preparation of amino-modified hollow glass microspheres, specifically comprising the following steps: S4.1: Particle size 5-10μm, wall thickness 0.5-1μm, density 0.15-0.25g / cm 3 The hollow glass microspheres are immersed in 5wt% dilute hydrochloric acid and ultrasonically treated for 20-30 minutes, then washed with deionized water until neutral, and dried at 90-100°C for 2-3 hours to obtain washed hollow glass microspheres; S4.2: γ-aminopropyltriethoxysilane and 60wt% ethanol aqueous solution are mixed in a volume ratio of 1:10-12, followed by magnetic stirring for 30-40 minutes, and the pH is adjusted to 5 with acetic acid to obtain a hydrolyzed silane solution; S4.3: Add 1-2 parts by weight of the washed hollow glass microspheres to 50-60 parts by weight of the hydrolyzed silane solution, and then stir the reaction at 60-70°C for 5-6 hours, and then centrifuge at 5000-6000 rpm for 5-10 minutes, and finally wash 2-3 times with one wash, and dry to obtain amino-modified hollow glass microspheres.
6. The preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass according to claim 5, characterized in that: Step S4 is the preparation of the heat-absorbing and heat-insulating coating, which specifically comprises the following steps: S5.1: 3-5 parts by weight of hydrophobically modified silica aerogel and 1-2 parts by weight of amino-modified hollow glass microspheres are placed in a planetary ball mill, using zirconia balls with a diameter of 3 mm, a ball-to-material ratio of 5:1, and ball milling at 300-500 rpm for 2-3 hours, with intervals of forward and reverse rotation, 10 minutes in the forward direction and 2 minutes in the reverse direction, then 0.5 wt% polyethylene glycol is added and ball milling is continued for 30-40 minutes to obtain a composite thermal insulation body after ball milling; S5.2: Mix 20-30 parts by weight of acrylic resin emulsion, 10-20 parts by weight of waterborne polyurethane, 0.05-0.12 parts by weight of polyester modified organosiloxane, 23-28 parts by weight of composite thermal insulation, 14-23 parts by weight of ferrosoferric oxide-copper manganese oxide core-shell structure particles, 3-9 parts by weight of fatty acid glyceride, 2-7 parts by weight of phenylethyl oleate and 12-18 parts by weight of deionized water, and stir to obtain a heat-absorbing and heat-insulating coating.
7. A heat-absorbing and heat-insulating coating for solar power generation glass, characterized in that: The heat-absorbing and heat-insulating coating is prepared by the preparation process of the heat-absorbing and heat-insulating coating for solar power generation glass as described in any one of claims 1 to 6.